Hate Speech Prosecution of Politicians and its Effect on Support for the Legal System and Democracy. Issue 2 (10th April 2022) - Rekker, Roderik; van Spanje, Joost
Abstract: This study examined if and for whom prosecution of politicians for hate speech undermines support for the legal system and democracy. Three research designs were combined to investigate the case of Dutch politician Geert Wilders, who was convicted for hate speech against minorities in 2016. First, an experiment showed that observing a guilty verdict decreased support among 'assimilationists' who oppose the multicultural society. This deterioration of support was found among the entire group of assimilationists, regardless of whether they voted for Wilders. Secondly, a quasi-experiment demonstrated that assimilationists who were interviewed after Wilders' conviction indicated less support than those who were interviewed before the verdict and compared to a pre-test. Thirdly, a nine-year panel study suggested that these effects accumulate into long-term discontent. This case therefore demonstrates that hate speech prosecution can damage the democratic system it is intended to defend.